Plan estratégico de la Empresa Sixma Compañía Agrícola S.A.”, del cantón Quevedo, provincia de Los Ríos, periodo 2012-2016 - Aguirre Miranda, Diana Mercedes (2012)
The present investigation project was carried out with the participation of the directive, administrative and operative personnel, with the purpose of carrying out the Strategic plan for the company Sixma Agricultural Company S.A., canton country Quevedo of The Ríos' ,for the period 2012-2016. Through this project one carries out the I diagnose situational administrative, objective to reach settled down to short and I release term, strategies were designed that will allow to reach their goals, excellent productivity and competing with quality and service. The strategic direction was structured, you proceeded to the preparation of administrations, programs, projects and operative plans. The investigation work executed it to him in the Treasury Happiness #2, having a population of forty six (46) field workers and four (4) administrative that are conformed for: The administrator, boss of field secretary of the Treasury Happiness #2 and the accountant of Sixma Agricultural Company S.A, in which was obtained important information of the strengths and weaknesses that are in the operative and administrative area by means of the development of a survey formed with closed questions and the interview elaboration toward the Manager Mr. Sixto Manobanda Álvarez. The results allowed to know the most outstanding problems, the personnel don’t have all the law benefits. The administrative personnel's 100% has work contract to fixed term, affiliation in the Ecuadorian Institute of Social security (I.E.S.S), they receive tenth third and quarter remuneration, however they don't perceive vacations, utilities, sure of health, sure of accident and jubilation. The field personnel's 100% has work contract to fixed term, 83% perceives the basic salary while 17% has the affiliation in the Ecuadorian Institute of Social security (I.E.S.S) the rest of the collaborators doesn't receive any benefit that the law aids. Limited training seminars since the administrative personnel's 25% has received in the countable area, however the operative personnel doesn't receive any training type to strengthen his position and the cautions that should take in the production processes and of environmental impact. It doesn't have a program of payment plan for the commercial partners for the inadequate use of the economic resources, they don't have designed the annual budget for the different administrative areas, the proposal was presented of elaborating budgets in order to determine what is hoped to spend and what will be obtained of the sales. They don't possess a strategic direction for that reason strategic objectives they have settled down, negotiate, strategies, programs, projects so that they contribute to the execution of the plan for such a reason one carries out the vision, mission, principles and organizational values so that they know each one of the members what the company wants to obtain and to maintain. It is required of obtaining new technologies that contribute for the inventory control in the productive processes, administrative in order to compete with excellence. As strength to maintain the certification of banana tree quality for Global-Gap fulfilling the procedures and norms that require, conserving the environment. By means of the preparation of this ideal it was determined the following conclusions: The company Sixma Agricultural Company S.A through this plan you design an analysis FODA in which consists to take advantage of their strengths, diminishing their weaknesses, to use their opportunities on time to be early before the threats of a competitive market. Settled down strategic objectives so that the organization has the administrative tools, it was designed programs, projects, administrations with the purpose that it is had vision, mission principles, organizational values to improve address of the same one. Was developed strategies that will allow to be more competitive in the market, leaving in advantage to potential competitors that will cover the national and international unsatisfied demand. This project allowed manifesting the following recommendations: Is fundamental that the company works continually in its strengths, execute action plans to reduce its weaknesses, invest in the opportunities that he/she offers the market being able to be more competitive, satisfying the world demand being early to the threats covering the expectations of the clients. Is disclosed the planning strategic with chats, seminars in order to obtain identity where they carry out its works in the same one that strategic objectives, vision, mission, principles and organizational values were executed. To execute the strategies that have been obtained by means of the administrative and operational analysis to take finishes the budgets in the different administrative areas, obtaining tip technology achieving surplus.